Greater levels of cardiorespiratory and muscular fitness are associated with low stress and high mental resources in normal but not overweight men - Kettunen O; Kyrolainen H; Santtila M; Vuorimaa T; Vasankari TJ (BIOMED CENTRAL LTD, 2026)
Background: The aim of the present study was to investigate how cardio respiratory (CRF) and muscular fitness (MF) together with leisure-time physical activity (LTPA) influence stress symptoms and mental resources among normal-weight and overweight men, because it is not known how body weight affects this association.Methods: In a cross-sectional study, 824 men (mean +/- SD: age 25 +/- 5 y, weight 81 +/- 13 kg, BMI 25 +/- 4 kg/m(2)) underwent CRF and MF tests and completed LTPA and stress questionnaires. For the analysis, the subjects were divided into BMI groups (normal vs. overweight) and CRF / MF / LTPA (low, moderate, high) tertiles.Results: Normal-weight men with low CRF reported 12 % (p = 0.001) more stress symptoms (SS) compared to normal-weight men with moderate CRF, and 13 % (p = 0.004) more SS compared to normal-weight men with high CRF. Normal-weight men with low MF reported 13 % (p = 0.001) higher SS compared to normal-weight men with moderate MF and 16 % (p = 0.002) more SS compared to men with high MF. Among overweight men, there were no significant differences in SS or mental resources (MR) between the low, moderate and high CRF and MF tertiles. Overweight men with high CRF experienced 8 % (p = 0.039) more SS compared to normal-weight participants with high CRF when age, tobacco and alcohol use, MF and LTPA were considered as covariates (p = 0.014).Conclusion: Higher CRF and MF are associated with lower stress and higher mental resources in normal-weight men, but in overweight men, these relationships may differ.